LETUSAN KRAKATAU 1883 DAN KORBAN-KORBANNYA DI DESA NELAYAN KARANGANTU BANTEN: SUATU KESAKSIAN ONG LENG YAUW - Romi Zarman (Universitas Andalas, 2013)
This article is based on Ong Leng Yauw’s testimony about Krakatoa eruption in 1883 and the victims in the Karangantu village Banten. Yauw Leng Ong is a Chinese, born and raised in Karangantu Beach Banten. He was 14 years old when the Krakatoa eruption occurred on August 27, 1883. From his testimony, the 1883 eruption of Krakatoa caused a tsunami that devastated Karangantu village Banten. Humans and animals corpses strewn among the rubble that blanketed the Krakatoa volcanic ash. There were only four survivors, Yauw Leng Ong, Ong Seng Boen, and two sisters Roti Nio and Biskoeit Nio.